1986
DOI: 10.1080/15298668691389423
|View full text |Cite
|
Sign up to set email alerts
|

Parameters that Bias the Measurement of Airborne Concentration Within a Respirator

Abstract: This paper describes the theoretical basis upon which a test system has been set up to evaluate the sampling error associated with in-facepiece sampling on half-mask respirators. The in-facepiece sampling technique evaluated in this study is the one currently used in the U.S. to conduct quantitative facepiece fit testing. An experimental design was developed to study the sampling bias associated with in-facepiece sampling when selected parameters of the man/respirator system were varied. The results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Higher sampling rate also reduces respirator purge time and significantly declines potential sampling bias especially for nonhomogeneous particles. (19,20) CONCLUSIONS T he N95 elastomeric and filtering facepiece respirators tested in the study provided expected level of respiratory protection for workers in agricultural farms. The 5th percentiles for the ER and FFR were higher than the APF of 10 and varied from 28 to 250 for ER, and from 16 to 223 for FFR.…”
Section: Resultsmentioning
confidence: 95%
“…Higher sampling rate also reduces respirator purge time and significantly declines potential sampling bias especially for nonhomogeneous particles. (19,20) CONCLUSIONS T he N95 elastomeric and filtering facepiece respirators tested in the study provided expected level of respiratory protection for workers in agricultural farms. The 5th percentiles for the ER and FFR were higher than the APF of 10 and varied from 28 to 250 for ER, and from 16 to 223 for FFR.…”
Section: Resultsmentioning
confidence: 95%
“…Sampling errors of Ϫ99 to ϩ98% have been demonstrated for in-facepiece aerosol sampling. (14) Particle loss in the needle or tubing used to induce the leak, leak geometry, and leak location appear to contribute to these biases. (9,14,16) Further, it has not been shown that any fixed leak location or geometry adequately represents leaks that occur during actual respirator use.…”
Section: Discussionmentioning
confidence: 95%
“…Potential concerns associated with fixed leaks include particle losses in the needle or tubing used to induce the leak, nonrepresentative leak geometry, and aerosol sampling bias associated with the choice of leak location. (9,14,15) Subjects initially were instructed to don the respirators according to manufacturers' instructions and perform a user seal check. However, after the first day of testing it was apparent that the user seal checks allowed experienced subjects to adjust nearly every facepiece such that an ''acceptable'' fit was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Insetting of the sample probe inlet by 1.0 to 1.5 cm has been recommended by some researchers. (8,9) The probe depth reduces the effects of mixing and the potential for the loss of sample on the inside wall of the respirator. The probe is placed directly in front of the mouth to further minimize the effects of mixing.…”
Section: Correction For Within-mask Sampling Biasmentioning
confidence: 99%